2022
DOI: 10.1038/s43018-022-00502-x
|View full text |Cite
|
Sign up to set email alerts
|

Potent high-avidity neutralizing antibodies and T cell responses after COVID-19 vaccination in individuals with B cell lymphoma and multiple myeloma

Abstract: Individuals with hematologic malignancies are at increased risk for severe coronavirus disease 2019 (COVID-19), yet profound analyses of COVID-19 vaccine-induced immunity are scarce. Here we present an observational study with expanded methodological analysis of a longitudinal, primarily BNT162b2 mRNA-vaccinated cohort of 60 infection-naive individuals with B cell lymphomas and multiple myeloma. We show that many of these individuals, despite markedly lower anti-spike IgG titers, rapidly develop potent infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 75 publications
3
15
1
Order By: Relevance
“…Recent evidence from the COVID-19 pandemic suggests that this population may derive a unique benefit from a vaccine strategy that drives a robust germinal center response. Studies of COVID-19 vaccine response in participants with hematologic neoplasia (lymphoma, myeloma) demonstrated that total IgG titers were substantially lower in this population following vaccination [37 ▪ ]. Surprisingly, both avidity and neutralization titers were higher in this population following vaccination as compared to healthy controls, especially at earlier time points, suggesting a more robust germinal center response.…”
Section: Trials In Immunocompromised Populations: Car-t Cell Recipientsmentioning
confidence: 77%
“…Recent evidence from the COVID-19 pandemic suggests that this population may derive a unique benefit from a vaccine strategy that drives a robust germinal center response. Studies of COVID-19 vaccine response in participants with hematologic neoplasia (lymphoma, myeloma) demonstrated that total IgG titers were substantially lower in this population following vaccination [37 ▪ ]. Surprisingly, both avidity and neutralization titers were higher in this population following vaccination as compared to healthy controls, especially at earlier time points, suggesting a more robust germinal center response.…”
Section: Trials In Immunocompromised Populations: Car-t Cell Recipientsmentioning
confidence: 77%
“…There are several caveats to the study by Keppler-Hafkemeyer et al 1 . The authors evaluated antibody avidity using a modified ELISA assay by adding a chaotropic agent to disrupt the hydrogen bonding between antigen and antibody, in order to elute antibodies that bind weakly to antigen.…”
Section: Published Online: 31 January 2023mentioning
confidence: 90%
“…Despite the tremendous amount of knowledge gained in COVID-19 research, there remains a lack of clarity about how to identify those who are most immunosuppressed and how best to prevent and treat severe COVID-19 infections. Keppler-Hafkemeyer et al 1 and Denkinger et al 10 highlight the importance of in-depth analysis when profiling immune responses to vaccination and the need for continued exploration of protective measures for immunosuppressed populations.…”
Section: Check For Updatesmentioning
confidence: 99%
See 2 more Smart Citations